CSR sposobem na trwałą przewagę konkurencyjną. Wpływ projektów realizowanych w Narodowych Strategicznych Ramach Odniesienia 2007-2013 na upowszechnienie społecznej odpowiedzialności biznesu w Polsce - Suska, Agnieszka (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
If a company wants to be innovative and competitive in the international market, it needs to act responsibly and have good relationships throughout the supply chain. Corporate social responsibility (CSR) is a management concept that addresses those challenges. The author attempted to identify the idea of CSR and relate it to the practical aspects. The projects supporting the development of CSR in Poland, which were implemented in the National Strategic Reference Framework 2007-2013, were analyzed. An attempt was made to assess the impact of projects co-financed from the Operational Program "Human Capital" on the promotion of CSR in Poland. The study was based on data from the National Information Infrastructure which collects information about contracts from the financial perspective 2007-2013